Answer:
x = -19/6
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Explanation:
Step 1: Define Equation
2x + 10 = -4x - 9
Step 2: Solve for x
- Add 4x on both sides: 6x + 10 = -9
- Subtract 10 on both sides: 6x = -19
- Divide 6 on both sides: x = -19/6
Step 3: Check
Plug in x into the original equation to verify it's a solution.
- Substitute in x: 2(-19/6) + 10 = -4(-19/6) - 9
- Multiply: -19/3 + 10 = 38/3 - 9
- Add/Subtract: 11/3 = 11/3
Here we see that 11/3 does indeed equal 11/3.
∴ x = -19/6 is the solution to the equation.